Current role of human leukocyte antigen matching in kidney transplantation - Süsal, Caner; Opelz, Gerhard (Current opinion in organ transplantation, 2013)
Purpose of review - With graft survival rates steadily improving during the recent years, there is debate whether donor kidneys should still be allocated according to compatibility for human leukocyte antigens (HLA). - Recent findings - Recent studies argue for continued kidney exchange efforts for achieving better HLA compatibility. In this modern era of immunosuppression, better HLA matching is associated not only with better graft survival, but also with the administration of lower dosages of immunosuppressive agents, a lower incidence of side-effects of immunosuppression such as non-Hodgkin lymphoma, hip fractures, and death from infection, and a lower grade of sensitization if a patient has lost a kidney graft and is relisted for a retransplant. - Summary - Despite the overall improved graft survival rates in the recent years, the data continue to support organ sharing based on HLA matching in kidney transplantation.